Exploring Ontology of Architectural Islamic Elements to Interpret Bliden Heritage Through Adaptive Patterns - Tiar Manel Djazia; Farhi Abdallah (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2024)
This article relates the traditional housing in an Algerian Islamic city called Blida. Its rich heritage is starting to disappear due to unaware destruction. To preserve its architectural heritage, we propose an experimental ontology of knowledge. It focuses on its mixed architecture's morphological and conceptual qualities to promote a new design adapted to the historic landscape. We have developed a heuristic method. It combines an analog approach with a digital tool. This method is structured from a spatio-temporal process for perceiving architectural language. The analysis of the characteristics begins through a morphological method constitutes the data collection phase of the ontology. Interpreting conceptual qualities concerning natural light is the second step for translation: the information phase. The development of operative paradigms constitutes the third stage for the perception of the learning phase. The resulting diagram illustrates the generative process with semantic modelling in a meaningful protocol. The result of morphology is representative sheets for artefacts, informed by its Morphological context and the sustainable design. Then, the result of the interpretation is the Eco models in qualified sheets represented through adaptive patterns. This protocol forms the conceptual basis of the knowledge ontology.